Campaña publicitaria para la concientización del abandono de los animales domésticos, en la zona urbana de la ciudad de Ambato - Martínez Naranjo, Christian Paúl (2023)
This project aims to provide an overview of the problem of animal abandonment, its impact on society and possible solutions to address this worrying situation. Animal abandonment is a problem that affects many countries around the world. It refers to the act of leaving pets or domestic animals in public places or on the street, depriving them of care and protection, which leads to a series of negative consequences both for animals and for society in general. The main objective of this project is the implementation of a media plan where apart from the creation of different advertising strategies. It is necessary to promote understanding and empathy towards animals, as well as implement practical measures to prevent the spread of this worrying situation. By taking concrete measures, where you can build a kinder and more respectful environment for all living beings.